The burden of diabetes in America: a data-driven analysis using power BI - Ekwebene, Onyeka Chukwudalu; Umeanowai, Ngozi Veronica; Edeh, Gabriel Chidera; Noah, Gideon Ugbeyo; Folasole, Adetayo; Olagunju, Olajide J.; Abazu, Somtochukwu (International Journal of Research in Medical Sciences, 2024)
Background: High blood glucose levels in diabetes lead to devastating damage to the heart, blood vessels, eyes, kidneys, and nerves. It affects millions of Americans and costs the healthcare system billions of dollars. The disease’s causes, risk factors, and effective prevention and treatment methods are still unknown despite its prevalence. Methods: This descriptive study used US census and CDC data to describe diabetes in America. The US census and CDC provided this study’s population and diabetes data. This study used two datasets. The first dataset contains 73054 2020 US population records. This dataset’s second type was strings and decimals, including state, county, and 2020 affected population percentage. Diabetics are represented by 3154 data points. Power BI was used to visualize decision support data. Results: According to our analysis, millions of Americans suffer from diabetes, which costs billions in healthcare costs annually. Diabetes is most prevalent in California, with 28.9 million people affected. Most cases are 45-64 years old, and the number has increased over the past decade. These findings suggest that America’s growing diabetes epidemic requires more resources and facilities. Conclusions: Finally, our study covers diabetes’s prevalence, incidence, and trends in America. Our findings show that America’s growing diabetes epidemic need more money, manpower, and infrastructure. We advise the government to monitor diabetes and plan for future healthcare needs.